International Rice Research Conference 2000 31 March - 3 April, Los Baños, Philippines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The following seven sessions are foreseen: 1. Increasing yield potential in irrigated rice: breaking the barrier2. Exploitation and utilisation of heterosis in rice 3. Breeding for abiotic stress tolerance4. Durable host-plant resistance 5....